Classification of public open spaces - Anuar, Aznamkhan; Mekhribanu, Glaudinova; Abdullah, Alias (2025)
of Public open spaces that meets modern requirements for comfort and sustainable development. The study employs a comparative analysis of existing scientific approaches, field observations, morphological examination of the urban fabric, and typologization of spatial structures. Methods of systematization, graphic-analytical modeling, and content analysis of project materials were applied. This methodological framework enables the identification of recurring spatial patterns and functional distinctions across different POS types. The proposed classification highlights key groups of Public open spaces based on functional specialization, scale, and degree of integration within the urban environment. Distinct spatial structures were identified, along with their characteristic features and formative factors. The findings emphasize the need for a comprehensive approach to POS development that considers spatial organization, social usage scenarios, and broader urban planning context. The study also acknowledges limitations related to insufficient statistical data and variations in terminology across research sources. Overall, the results demonstrate the importance of creating a unified classification capable of improving the planning, design, and management of open public spaces. The insights gained may inform future urban planning strategies and serve as a foundation for further research.